A study of contents and services of the academic library web sites in the Philippines its present state and future developments - Cabunagan, Ronald Jess C. (2001)
For the last few years, the Internet has expanded rapidly in terms of size and popularity that it has become into a major platform for networking and information provision. The most popular feature of the Internet, the World Wide Web enables features such as interlinking, multimedia and interactivity, making it an another medium with which the library can fulfill its traditional functions.